2008
DOI: 10.1111/j.1471-0528.2008.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of severe obstetric haemorrhage

Abstract: Objective To determine the prevalence, causes, risk factors and acute maternal complications of severe obstetric haemorrhage.Design Population-based registry study.Population All women giving birth (307 415) from 1 January 1999 to 30 April 2004 registered in the Medical Birth Registry of Norway. Information about socio-economic risk factors was obtained from Statistics Norway.Methods Cross-tabulation was used to study prevalence, causes and acute maternal complications of severe obstetric haemorrhage. Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
227
7
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(268 citation statements)
references
References 45 publications
25
227
7
5
Order By: Relevance
“…Cesarean delivery is a well-recognized risk factor for severe PPH [13]. Among the women who had a vaginal delivery, a greater proportion of the cases underwent an operative vaginal delivery, another well-recognized risk factor for PPH [5,7,13]. We found that certain factors that may impair uterine contractility and affect systemic hemostasis were also risk factors for severe PPH.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Cesarean delivery is a well-recognized risk factor for severe PPH [13]. Among the women who had a vaginal delivery, a greater proportion of the cases underwent an operative vaginal delivery, another well-recognized risk factor for PPH [5,7,13]. We found that certain factors that may impair uterine contractility and affect systemic hemostasis were also risk factors for severe PPH.…”
Section: Discussionmentioning
confidence: 78%
“…While we controlled for mode of delivery (vaginal delivery vs. cesarean delivery before labor vs. cesarean delivery after labor), women who experienced severe PPH, had a higher rate of cesarean delivery (57%), compared to the cesarean delivery rate at our institution. Cesarean delivery is a well-recognized risk factor for severe PPH [13]. Among the women who had a vaginal delivery, a greater proportion of the cases underwent an operative vaginal delivery, another well-recognized risk factor for PPH [5,7,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La incidencia de hemorragia obstétrica en el presente estudio fue de 2,1 %, menor a la reportada en la literatura mundial (4-6 %), y a la reportada previamente para la institución (1,3,8,13). La incidencia establecida por el empleo de medicamentos adicionales al manejo activo del alumbramiento, una vez excluidas las mujeres en las que se anotó la utilización preventiva de los uterotónicos posparto, fue 3,5 veces la incidencia reportada según la definición de caso utilizada por el Sistema de Vigilancia Epidemiológica (SIVIGILA).…”
Section: Discussionunclassified
“…factors identified antenatally may have a subsequent increased incidence of PPH whereas other high risk features may become apparent during labour and delivery, e.g., prolonged labour, and emergency caesarian section (Al-Zirqi et al, 2008). A recent study (Cook et al, 2013) has highlighted that women with multiple repeat caesarian section are at a significantly greater risk of MOH >1500 ml) [adjusted odds ratio (aOR), 18Á6; 95% confidence interval (CI), 3Á89-88Á8].…”
Section: Definition Of Mohmentioning
confidence: 99%